2022
DOI: 10.3892/etm.2022.11278
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of indolence in prostate cancer (Review)

Abstract: Although prostate cancer is a major cause of cancer-related mortality worldwide, most patients will have a relatively indolent clinical course. Contrary to most other types of cancer, even the diagnosis of locally advanced or metastatic disease is not always lethal. The present review aimed to summarize what is known regarding the underlying mechanisms related to the indolent course of subsets of prostate cancer, at various stages. The data suggested that no specific gene alteration by itself was responsible f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 147 publications
(147 reference statements)
0
8
0
Order By: Relevance
“…Hereby, the question regarding the effect of cells in a quiescence state arises. This quiescence state is known to be important for tumor cells to develop new evasive mechanisms through genomic changes ( 49 , 50 ). The effect of PARPi in quiescent PCa cells is currently not known.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Hereby, the question regarding the effect of cells in a quiescence state arises. This quiescence state is known to be important for tumor cells to develop new evasive mechanisms through genomic changes ( 49 , 50 ). The effect of PARPi in quiescent PCa cells is currently not known.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Pathogenic mutation in the DDR genes BRCA1/2 and ATM status differs between risk for aggressive and indolent PCa and is linked to a younger death age and a shorter survival period ( Na et al, 2017 ). According to research, while some people have aggressive cancers that metastasize and result in disease-related death, many with indolent tumors can be successfully treated with early therapy or monitored ( Sakellakis et al, 2022 ). Furthermore, studies conducted in various contexts with various populations have demonstrated that homologous recombination repair (HRR) and mismatch repair genes, which are mutated in a high proportion of patients, are involved in aggressive PCa biology ( Lukashchuk et al, 2023 ).…”
Section: Clinical and Therapeutic Implications Of Dna Damage Response...mentioning
confidence: 99%
“…Accurate prediction of post-RP BCR requires long-term follow-up (>10 years) owing to the high variability of BCR events and PCa’s slow-growing and often indolent nature [ 37 , 38 ]. More importantly, the characteristics of PCa exhibit regional and ethnic variations, suggesting that race- and nation-specific characteristics of PCa should be considered for developing a more accurate prediction model.…”
Section: Introductionmentioning
confidence: 99%